The effect of age and gender as moderators towards the relationship between customer satisfaction and revisit intention: a study on tea house setting / Zuratulraha Jaafar, Hairunnisa Mohamad Ibrahim and Siti Nor Fadillah Ahmad Shariff - Jaafar, Zuratulraha; Mohamad Ibrahim, Hairunnisa; Ahmad Shariff, Siti Nor Fadillah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Retaining present customers and ensuring repeat trips and purchases is critical for any food service operator. Drawing on the recent trend and taking the case of teahouses, this study explores the teahouse customers’ satisfaction and revisits intention by analyzing age and gender as moderator factors. The author utilizes regression analysis to test the proposed causal relationships. The result analytically confirmed that satisfaction with service, product, social factors, ambiance, and location are the backgrounds of repeat intention of teahouses. Age and gender were found to moderate the effect of customer satisfaction and revisit intention. The findings encourage teahouse operators to take good measures in drawing more repeat customers to their premises.